Long-term results of Perioperative High Dose Rate Brachytherapy (PHDRB) and external beam radiation in adult patients with soft tissue sarcomas of the extremities and the superficial trunk: Final results of a prospective controlled study. (June 2019) - Gimeno, Marta; San Julián, Mikel; Cambeiro, Mauricio; Arbea, Leire; Jablonska, Paola; Moreno-Jiménez, Marta; Amillo, Santiago; Aristu, Javier; Lecanda, Fernando; Martinez-Monge, Rafael
Highlights: This prospective study included 106 adults extremities and superficial trunk STS. The treatment protocol consists of surgical resection, PHDRB, EBRT+/−chemotherapy. The results show adequate function and local control in the majority of the patients. Despite having 72% of close/positive margins, only 10% of local failure is reported. Grade ≥3 toxicity occurs in nearly 30% of the cases and is related to implant volume. Patients with larger tumors has higher risk of complications and treatment failure. Individualized treatment approach must be considered on patients with larger tumors. Abstract: Background: To analyze toxicity, patterns of failure, and survival in 106 adult patients with soft tissue sarcomas of the extremity and the superficial trunk treated in a prospective controlled trial of combined Perioperative High Dose Rate Brachytherapy (PHDRB) and external beam radiotherapy (EBRT). Methods: Patients were treated with surgical resection and 16 Gy or 24 Gy of PHDRB for negative or close/positive margins, respectively. EBRT (45 Gy) was added postoperatively. Adjuvant chemotherapy was given to selected patients with high-grade tumors. Results: The median follow-up was 7.1 years (range, 0.6–16.0). Grade ≥3 adverse events were observed in 22 patients (20.8%), and grade ≥4 events in 14 patients (13.2%). No grade 5 events were noted. Multivariate analysis (p = 0.003) found that Grade ≥3 toxic events increased with increasing implant volume (TV100 ). Local control, locoregional control, and distant control rates at 5 and 10 years were 89% and 87%, 82% and 80% and 75% and 69%, respectively. Multivariate analysis (p = 0.024) found that positive margins correlated with decreased local control. Disease-free survival and overall survival rates at 5 and 10 years were 64% and 59% and 73% and 62%, respectively. In multivariate analysis, disease-free survival rates decreased with increasing tumor size (p = 0.0001) and inadequate margins (p = 0.024), and overall survival decreased with increasing tumor size (p = 0.001) and male gender (p = 0.039). Conclusions: The combination of conservative surgery, high-dose PHDRB, and EBRT produces adequate function and local control in the majority of patients with soft tissue sarcomas of the extremities and the superficial trunk, including a substantial percentage of cases with positive margins. Patients with larger tumors are at a higher risk of complications, treatment failure, and cancer-related death and require an individualized treatment approach.